Environmental Fate of Neonicotinoids and Classification of Their Potential Risks to Hypogean, Epygean, and Surface Water Ecosystems in Brazil - Miranda, Gustavo R. B.; Raetano, Carlos Gilberto [UNESP]; Silva, Emilia; Daam, Michiel A.; Cerejeira, Maria Jose (Taylor & Francis Inc, 2011)
Due to their reported high toxicity to honey bees, ecotoxicological studies into the side-effects of neonicotinoid insecticides have focused almost exclusively on these organisms. The fate of neonicotinoids and potential toxic side-effects on other (especially non-standard) organisms have received considerably less attention. In the present study, the environmental distribution and leaching potential of neonicotinoids registered for agricultural use in Brazil (acetamiprid, clothianidin, imidacloprid, thiacloprid, and thiamethoxam) were studied by applying several environmental fate models and indices. Potential risks to various environmental compartments were evaluated by applying ranking indices to the maximum application rates recommended in Brazil. Although bees were indeed found to be the most sensitive organism, the neonicotinoids also indicated potential environmental risks to other organism groups. Due to the greater maximum application rates recommended in Brazil as compared to other parts of the world, environmental risk and resistance potential for at least imidacloprid appears especially high in Brazil. Attention should thus also be allocated to organisms other than bees and to resistance potential when performing an environmental risk assessment of neonicotinoids if they are used at relatively high application rates.
Keywords: neonicotinoids; fate; environmental risk; resistance; Brazil; tropics